1978
DOI: 10.1093/bja/50.11.1099
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CERTAIN ANAESTHETIC AGENTS ON THE ACTIVITY OF RAT HEPATIC Δ-Aminolaevulinate SYNTHASE

Abstract: The activity of delta-aminolaevulinic acid synthase (E.C.2.3.1.37) (the rate-limiting enzyme for haem and porphyrin biosynthesis) has been measured in the rat liver after the repeated administration of anaesthetic agents in vivo. The activity of the enzyme was increased by Althesin, chlordiazepoxide, enflurane, etomidate, lignocaine, methohexitone, methoxyflurane, pentazocine and thiopentone and decreased by procaine. No significant changes in activity occurred after the administration of amethocaine, atropine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…The liver was then excised, chilled in ice and blotted dry. Aliquots were taken and weighed for ALA synthase and cytochrome P450 determination by the methods of Parikh & Moore (1978) and Omura & Sato (1964) respectively. Heparinized venous blood (30 ml) was required for the determination of the leucocyte ALA synthase activity.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The liver was then excised, chilled in ice and blotted dry. Aliquots were taken and weighed for ALA synthase and cytochrome P450 determination by the methods of Parikh & Moore (1978) and Omura & Sato (1964) respectively. Heparinized venous blood (30 ml) was required for the determination of the leucocyte ALA synthase activity.…”
Section: Animal Studiesmentioning
confidence: 99%
“…We speculate that the epidural analgesia was effective in reducing not only surgical stress during operation but also postoperative pain, and that it resulted in the absence of acute attack. Parikh and Moore examined various agents in a rat model which suggested that procaine and bupivacaine are safe agents, but that lidocaine should be avoided [16]. There is no evidence that the use of bupivacaine in a regional anesthetic technique precipitates an attack of acute intermittent porphyria [6].…”
Section: Discussionmentioning
confidence: 99%
“…Lange Zeit wurde [14,16]. Den Berichten einer möglichen Assoziation mit Halothanapplikation widersprechen experimentelle und klinische Erfahrungen [7,13,21].Im Tierversuch konnte Enfluran als porphyrinogen identifiziert werden [4,22]; es fehlen aber klinische Korrelationen. Isofluran erscheint aufgrund einiger Berichte [4,7,14,16,17,21] als sicher; allerdings sollten noch weitere Daten erhoben werden [14,16].…”
Section: Desflurane In Acute Intermittent Porphyriaunclassified
“…Da wir in unserem perioperativen anästhe-siologischen Management die frühzeiti-ge Extubation bei absoluter Schmerzfreiheit anstrebten, entschlossen wir uns, einen thorakalen Periduralkatheter bei Th 8/9 zu legen.Der neurologische Status der Patientin wurde vorher durch einen Neurologen dokumentiert. Wir verwendeten Bupivacain, das als sicher gilt [14,22]. Die spinale Testung erfolgte mit 3 ml 0,5%igem Bupivacain.Auf eine Hauptdosis zum Hautschnitt verzichteten wir bewusst, um eine hämodynamische Instabilität bei evtl.…”
Section: Postoperativer Verlauf Der Porphyrinpräkursorenunclassified